2015
DOI: 10.1002/bit.25613
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of Clostridium tyrobutyricum for n‐butanol production through co‐utilization of glucose and xylose

Abstract: The glucose-mediated carbon catabolite repression (CCR) in Clostridium tyrobutyricum impedes efficient utilization of xylose present in lignocellulosic biomass hydrolysates. In order to relieve the CCR and enhance xylose utilization, three genes (xylT, xylA, and xylB) encoding a xylose proton-symporter, a xylose isomerase and a xylulokinase, respectively, from Clostridium acetobutylicum ATCC 824 were co-overexpressed with aldehyde/alcohol dehydrogenase (adhE2) in C. tyrobutyricum (Δack). Compared to the strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(21 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Because of the requirement of extra energy in xylose transport, the net ATP yield from xylose was lower compared to that from glucose [ 13 , 14 ]. Although glucose metabolism can provide more ATP for cell growth and butyric acid production, glucose-mediated carbon catabolite repression (CCR) could inhibit the consumption of non-glucose sugars such as xylose also present in the lignocellulosic biomass hydrolysate [ 12 , 20 , 40 ]. Xylose utilization by C. tyrobutyricum was inhibited by glucose in free-cell fermentation, although the CCR could be relieved by engineering the cell to overexpress three genes in the xylose catabolism pathway [ 12 , 20 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the requirement of extra energy in xylose transport, the net ATP yield from xylose was lower compared to that from glucose [ 13 , 14 ]. Although glucose metabolism can provide more ATP for cell growth and butyric acid production, glucose-mediated carbon catabolite repression (CCR) could inhibit the consumption of non-glucose sugars such as xylose also present in the lignocellulosic biomass hydrolysate [ 12 , 20 , 40 ]. Xylose utilization by C. tyrobutyricum was inhibited by glucose in free-cell fermentation, although the CCR could be relieved by engineering the cell to overexpress three genes in the xylose catabolism pathway [ 12 , 20 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although glucose metabolism can provide more ATP for cell growth and butyric acid production, glucose-mediated carbon catabolite repression (CCR) could inhibit the consumption of non-glucose sugars such as xylose also present in the lignocellulosic biomass hydrolysate [ 12 , 20 , 40 ]. Xylose utilization by C. tyrobutyricum was inhibited by glucose in free-cell fermentation, although the CCR could be relieved by engineering the cell to overexpress three genes in the xylose catabolism pathway [ 12 , 20 , 40 ]. However, our results indicated that glucose mediated CCR would have little effect on butyric acid production from corn husk hydrolysate after cell adaptation in the FBB.…”
Section: Discussionmentioning
confidence: 99%
“…1-Butanol titers from E. coli and Clostridium species are comparable. Recently reported engineered Clostridium species utilizing acetone-butanol-ethanol fermentation have been able to produce 19.1 g/L within 78 h (Xue et al, 2012), or 15.7 g/ L using co-utilization of glucose and xylose (Yu et al, 2015). The titer reported here is much higher compared to other non-native hosts such as in Saccharomyces cerevisiae (835 mg/L in 96 h) (Shi et al, 2016), cyanobacterium Synechococcus elongatus PCC 7942 (404 mg/L in 12 days) (Lan et al, 2013) and Lactobacillus brevis (300 mg/L in 60 h) (Berezina et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is still a need to develop a consolidated bioprocessing technology for butanol production. Note that sustainable butanol production is also impeded by (i) product inhibition and carbon catabolite repression (CCR) ( 20 ) and (ii) complexities of downstream purification of butanol from other by-products such as acetone and ethanol ( 21 ). Hence, to achieve and simplify the consolidated bioprocessing, it is desirable to discover bacterial strains that can directly ferment cellulose and hemicellulose to butanol as the main product.…”
Section: Introductionmentioning
confidence: 99%